Polish Version of the Resilience Scale (RS-14): A Validity and Reliability Study in Three Samples - Surzykiewicz, Janusz; Konaszewski, Karol; Wagnild, Gail (Frontiers in Psychology, 2019)
There has been a need for an instrument which not only can adequately evaluate trait-like resilience, but also can be applied to Polish adolescents and young adults. The purpose of this study was to validate the Resilience Scale RS-14 (Wagnild, 2009, 2010). We aimed to examine and assess the psychometric properties of the Polish version in three different samples. The first sample was made up of adolescents aged 13 to 17 (N=400).The second sample was made up of a problem group aged 13 to 18 (N=656) who had special needs and attended either Probation Centers, Youth Sociotherapy Centers, or Youth Educational Centers. The third sample was made up of students in early adulthood aged 19 to 27 (N=1659). Exploratory and confirmatory factor-analytic methods were employed. CFA demonstrated a good fit of the factor structure in all three samples. The original one-dimensional structure of the RS short form was confirmed. All items loaded (>.0.40) onto 1 factor, indicating cohesive structure for a 1-factor model explaining 35.02% of the variance in the whole sample, 34.62% in the young adolescent sample, 31.11% in the problem sample, and 38.51% in the early adulthood sample. Descriptive statistics, reliability (young adolescence α=0,85, problem sampleα=0,82 early adulthood α=0,87) and validity data were calculated; test-retest showed good stability (r(40)=0.88; p<0.001) and Polish norms were also established. The convergent and divergent validity of the scale RS-14 was applied in two groups (the N=382 early adulthood aged 19 to 27,and the N=120 problem group aged 13 to 18) and was subsequently evaluated. The RS-14 correlated significantly, as expected, with measures of positive concepts (satisfaction with life). Results showed that resilience was negatively relatedwith indexes of perceived stress and the dimension-of-depression. Findings support the RS-14 to be a valid and useful instrument for assessing resilience in diverse Polish adolescent groups, including those with special needs and those in early adulthood.